Technological promotion: a policy opportunity for provision of technical supports to small and medium enterprises in Vietnam - Hung, Nguyen Vo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
The paper provides theoretical backgrounds of technological promotion, a policy of direct supports to enterprises for stimulation of modernization and improvement of technologies with the main attentions focused on well formed small and medium enterprises, a clear identification of scope and subjective figures of technological promotion in policy space and highlighting of approaches based on modes of “hands-on indicating” and “oriented targeting” of technological promotion for enterprises. Analizing programs and organizations conducting certain technical supports for small and medium enterprises, the paper indicates that they, once based on State organizations, State staffs, State budgets and the so-called “begging-granting” practice, are difficult to arrive to “oriented targets” - large number of small and medium enterprises, the scope of impacts of these programes being not found enough large and deep. At the same time, these limitations show that the technological promotion is a policy opportunity with full potentials for use. The paper proposes an idea to design a technological promotion program in Vietnam based on network linkage with the core role of local technological promotion centers. The main principle here is the use of publicprivate partnership mechanisms for promotion of professional and dynamique supply of services and the use of public-public cooperation mechanism for mobilization of resources from line ministries, local bodies, international organizations, programs and projects which have targets to support small and medium enterprises. The idea of this design is relatively novel in Vietnam then naturally may lead to eventual conflicts and hitches with existing policies and mechanims. The paper also hints some directions to settle these hitches. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"> Code: 19060401